An Experimental Study of a Conventional Cylindrical Oscillating Water Column Wave Energy Converter: Fixed and Floating Devices - Wanan Sheng; George Aggidis (Energies)
Oscillating water column (OWC) wave energy converters (WECs) are very popular types of wave energy converters due to their practical implementations, their versatility in deployment in different marine environments, and their high reliability in wave energy conversion. In development, different forms of OWCs have been proposed and advanced, such as fixed OWCs (on the shoreline, on breakwaters, or bottom standing) and floating OWCs (the spar and the backward-bent duct buoy, BBDB). In reality, a special type of OWC, the cylindrical OWC, is the simplest OWC in terms of its structural design and possible analytical/numerical solutions. However, such a simple OWC has not seen any practical applications because a cylindrical OWC is inefficient in wave energy absorption when compared to other types of OWC WECs. To study the simplest cylindric OWC, an experiment was carried out in a wave tank, and the relevant results are presented in this paper, with the aims of (i) analyzing the experimental data and exploring why such an OWC is inefficient in terms of wave energy absorption; (ii) providing experimental data for those who want experimental data to validate their numerical models; and (iii) establishing a baseline model so that comparisons can be made for improvements to the simple cylindrical OWC. As an example, an innovative solution was applied to the simple OWC such that its hydrodynamics and energy extraction performance can be significantly improved (the corresponding results will be presented in a separate paper).